All types of atrial fibrillation in the setting of myocardial infarction are associated with impaired outcome. Issue 12 (29th February 2016) - Batra, Gorav; Svennblad, Bodil; Held, Claes; Jernberg, Tomas; Johanson, Per; Wallentin, Lars; Oldgren, Jonas
Abstract : Objectives: To evaluate 90-day cardiovascular outcome in patients after myocardial infarction (MI) in relation to different subtypes of atrial fibrillation (AF) and MI. Methods: We studied 155 071 hospital survivors of MI between 2000 and 2009 in Swedish registries. AF subtypes were defined according to history of AF and in-hospital ECG recordings. Clinical outcomes were evaluated with multivariable Cox models. Results: AF was documented in 24 023 (15.5%) cases. The AF subtypes were new-onset AF with sinus rhythm at discharge (3.7%), new-onset AF with AF at discharge (3.9%), paroxysmal AF (4.9%) and chronic AF (3.0%). The event rate per 100 person-years for the composite cardiovascular outcome (all-cause mortality, MI or ischaemic stroke) was 90.9 in patients with any type of AF versus 45.2 in patients with sinus rhythm, adjusted hazard ratio with 95% CI (HR) 1.28 (1.19 to 1.37). There were no significant differences in the composite cardiovascular outcome between AF subtypes. AF was associated with higher risk of mortality, HR 1.59 (1.41 to 1.80), reinfarction, HR 1.14 (1.05 to 1.24), and ischaemic stroke, HR 2.29 (1.92 to 2.74), respectively. In subgroup analysis, AF was associated with a higher risk of composite cardiovascular outcome in the non-ST-elevation myocardial infarction (NSTEMI) and ST-elevation myocardial infarction (STEMI) cohort, HR 1.24 (1.13 to 1.36) and HR 1.34 (1.21 to 1.48), respectively, with p value for interaction=0.23. Conclusions: AF is common in the setting of MI and is associated with a higher risk of composite cardiovascular outcome and the individual components; mortality, reinfarction and ischaemic stroke, respectively. No major difference in outcome was observed between AF subtypes. No difference in outcome for AF was observed between the NSTEMI and STEMI cohort.